2017
DOI: 10.2527/jas.2016.1072
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the interaction of forage and supplement type on digestibility and ruminal fermentation in beef cattle1

Abstract: The objectives of this research were to test interactions of supplement type, liquid versus dry, and forage type, hay versus corn stover, on digestibility and ruminal metabolism of beef cattle. Ruminally fistulated steers were fed in a replicated 4 × 4 Latin square with a 2 × 2 factorial arrangement of treatments: 1) hay with liquid supplement, 2) hay with dry supplement, 3) corn stover with liquid supplement, and 4) corn stover with dry supplement. The liquid supplement was molasses and glycerin based (23.3% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…These results could be related to the fermentation treatment and quality among the forage, as well as to the inclusion level in the diets. High-quality forage usually has a high digestibility due to the increased ruminal degradability of structural cell walls, in which low concentrations of cell wall polysaccharides and lignin accumulate (Stierwalt et al, 2017). The present results indicated that the dry peanut vine, peanut vine silage, and the combination of dry peanut vine with corn silage as forage sources exhibited similar growth performance in Holstein bulls.…”
Section: Intake and Growth Performancesupporting
confidence: 49%
“…These results could be related to the fermentation treatment and quality among the forage, as well as to the inclusion level in the diets. High-quality forage usually has a high digestibility due to the increased ruminal degradability of structural cell walls, in which low concentrations of cell wall polysaccharides and lignin accumulate (Stierwalt et al, 2017). The present results indicated that the dry peanut vine, peanut vine silage, and the combination of dry peanut vine with corn silage as forage sources exhibited similar growth performance in Holstein bulls.…”
Section: Intake and Growth Performancesupporting
confidence: 49%
“…(1) Among these, corn stover is the most readily available crop residue used as feedstock for cattle. Although it has a low nutritional value, (2) ruminants can transform these low-quality forages into milk and meat for human consumption. This transformation is due to the fermentation process carried out by the ruminal microbial population, which is composed of bacteria, archaea, protozoa, fungi, and viruses.…”
Section: Introductionmentioning
confidence: 99%